MEASUREMENTS COMBINATION OF ELASTIC ANISOTROPY AND ANISOTROPY OF MAGNETIC SUSEPTIBILITY ON THE CASE STUDY IN IGNEOUS ROCK OF LAVA FLOW TYPE FROM BATUR GLOBAL GEOPARK, BALI - Rantri Desi Wulan Ndari, Nuresi
Knowledge about anisotropy property of rock is very important for geophysical investigations. This research is a preliminary study which aims to find the relationship between seismic (elastic) anisotropy and anisotropy of magnetic susceptibility (AMS) in igneous rock of lava flow type from Mount Batur and also to interpret preferred orientation in the igneous rock of lava flow type based on the integration of anisotropy measurement results with the supported results from microcomputed tomography (?CT) analysis, petrography analysis and geological data. This research has never been done before. The distinction of this research is the combination of four methods which usually work independently into new method used to interpret preferred orientation in rock with more accurately. This study will be divided into several stages consist of field activities to get the samples, preparation of measurements samples, seismic wave velocity measurements (Vp and Vs) on three main perpendicular axes of cube-shaped samples to get the direction of maximum velocity and elastic anisotropy parameter values, magnetic susceptibility measurements on six directions for each core sample to determine the direction of the maximum magnetic suseptibility axis (magnetic mineral orientation) and AMS parameter values, petrography analysis to observe preferred mineral orientation and ?CT analysis in core sample to examine the porosity trend of rocks. In this study the authors will use six samples with BTR2 - BTR7 code, which are lava product from Mount Batur eruption in 1849. AMS measurements show a consistent results on all rock samples where the direction of maximum magnetic susceptibility axis are parallel with the flow direction, namely NE-SW. Based on the results, the elastic anisotropy degree of rocks ranges from 6.39% - 25.98% and anisotropy of magnetic susceptibility degree of rocks ranges from 3.68% - 6.11%. There is no significant correlation that was found between these two anisotropy probably because elastic anisotropy was more influenced by local factors. Elastic anisotropy is more correlated with rock pores, showed by strong negative correlation between seismic velocity values and pore percentages namely -0.83. Likewise with the anisotropy of magnetic susceptibility, three out of six samples showed a positive correlation between AMS and preferred pore orientation, where both parameters point to the northeast direction. The difference in the position of the sample in a lava flow was observed as a possible factor that influenced the results for the preferred pore orientations. Samples taken from the center / summit of the lava flow will have pores orientation which parallel with lava flow direction. While samples that taken from the slope of the lava flow, will have pores orientation which perpendicular with lava flow direction.